Islam and Socialism in Indonesia: The Influence of HOS Tjokroaminoto's Thoughts on Agus Salim - Taufiqurrahman, Taufiqurrahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This paper examines the intersection of Islam and socialism in Indonesia, focusing on the intellectual lineage from HOS Tjokroaminoto to Agus Salim. Both figures played pivotal roles in shaping Indonesia's political landscape during the early 20th century. Tjokroaminoto, a prominent Islamic scholar and nationalist leader, was instrumental in synthesizing Islamic principles with socialist ideals. His efforts sought to address socio-economic disparities and advocate for the rights of the common people. Agus Salim, a prominent diplomat and intellectual contemporary of Tjokroaminoto, was deeply influenced by the latter's thoughts on the harmonious integration of Islam and socialism. The type of research used is literature research, with data sources from the study of books related to Islamic socialism by Tjokroaminoto and Agus Salim. The research results show that there are three types of Tjokro's thoughts towards Agus Salim that are used as the outline of the Sarekat Islam movement: the first is the freedom of the people, the second is equality, and the third is love for the homeland and anti-capitalism. Leadership is an interpretation of its people, according to the leadership philosophy taught by Agus Salim to his political disciple Kasman Singodimedjo. Therefore, leaders must prioritize the people's interests above all else, or